Assessing the Impact of Underwater Clearance of Unexploded Ordnance on Harbour Porpoises (Phocoena phocoena) in the Southern North Sea - von Benda-Beckmann, A.; Aarts, G.; Sertlek, H.; Lucke, Klaus; Verboom, W.; Kastelein, R.; Ketten, D.; van Bemmelen, R.; Lam, F.; Kirkwood, R.; Ainslie, M. (EUROPEAN ASSOC AQUATIC MAMMALS, 2015)
Large amounts of legacy unexploded ordnance (UXO) are still present in the North Sea. UXO are frequently accidentally encountered by fishermen and dredging vessels. Out of concern for human safety and to avoid damage to equipment and infrastructure from uncontrolled explosions, most reported UXO found in the Dutch Continental Shelf (DCS) are detonated in a controlled way. These underwater detonations produce high amplitude shock waves that may adversely affect marine mammals. The most abundant marine mammal in the DCS is the harbour porpoise (Phocoena phocoena), a species demonstrated to be highly sensitive to sound. Therefore, an assessment of potential impacts of underwater explosions on harbour porpoises was undertaken. Information regarding UXO cleared in the DCS provided by the Netherlands Ministry of Defence was used in a propagation model to produce sound exposure maps. These were combined with estimates of exposure levels predicted to cause hearing loss in harbour porpoises and survey-based models of harbour porpoise seasonal distribution on the DCS. It was estimated that in a 1-y period, the 88 explosions that occurred in the DCS very likely caused 1,280, and possibly up to 5,450, permanent hearing loss events (i.e., instances of a harbour porpoise predicted to have received sufficient sound exposure to cause permanent hearing loss). This study is the first to address the impacts of underwater explosions on the population scale of a marine mammal species. The methodology is applicable to other studies on the effects of underwater explosions on the marine environment.